Innovation and economic performance in MENA region - Noha Sami Omar (Review of Economics and Political Science (REPS), 2019)
Purpose - Innovation has become the engine of economic growth, especially with the Fourth Industrial Revolution. This paper aims at studying the association between innovation - measured by gross expenditure on research and development (GERD) - and economic performance - represented by real gross domestic product (GDP) - in MENA region over the period 1996-2016. Design/methodology/approach - The paper uses the panel corrected standard error method to account for heteroskedacity and possible contemporaneous correlation across panels, and the first order autocorrelation within panel for unbalanced datasets. Findings - The study concludes that R&D expenditure is positive and statistically significant in explaining GDP, but their relationship is weak. Specifically, a 10 per cent increase in R&D expenditure raises GDP by 4 per cent. In addition, human capital, labor force and fixed capital accumulation are found positive and statistically significant. These findings highlight on the importance of innovation and education on fostering economic growth, urging MENA governments to further invest in R&D and innovation sector. Originality/value - To the best of the author's knowledge, this paper is the first to investigate the relationship between GERD and GDP in MENA region within the endogenous-growth model framework.
Keywords: 330; Innovation; MENA